Pelatihan Jurnalistik dalam Membangun Literasi Media pada Anak-Anak di Sanggar Ar-Rosyid Purwokerto - Adita Miranti; Ade Tuti Turistiati; Prita Suci Nurcandrani; Audito Anindya Bayu Aji; Raja Satria Wibawa; Anggita Ramadisa (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
The number of children who overuse the device makes them less creative in writing and telling stories. In addition, children sometimes access news that is not suitable for them, such as scenes of violence, pornography, and porno-action. This condition also occurs in children in Ar-Rosyid Purwokerto. Community Service Program (PKM) in the form of journalistic training is conducted to build media literacy by developing children's creativity in the field of journalism, both in the form of writing and in the form of broadcasts.This training was held by lecturers and students of the Communication Studies Program at Universitas Amikom Purwokerto in mid September and October 2019 (every Saturdays). There were 20 elementary and junior high school students participated in this training. They joined the non-formal activities in Ar-Rosyid Purwokerto. The facilitators assisted the participants and provided them with knowledge and skills related to the journalistic principles and elements. The participants gained knowledge and skills on how to conduct interviews and observation, and write news according to journalistic rules. In addition, the participants gained experience about the radio broadcasting process and making journalism photos. The training started from the orientation, introduction of journalism for children, journalistic practices for children, practice, and evaluation. All steps were carried out at Universitas Amikom Purwokerto.After the training, the participants' interest in writing article and stories are improving. The participants can write free themes using journalistic elements. In additions, they are confident to do deliver their simple speech in front of audience as well as in the radio broadcasting.